Age matching patterns and search - Anja Sautmann (Brown University, Department of Economics, 2010)
Consider a marriage market with continuous-time two-sided search and transferable utility in which the match payoff depends on age. This paper characterizes a set of payoff functions consistent with two salient marriage age patterns: (1) assortative matching by age, and (2) age matching, a formalization of the age difference at marriage between men and women. The payoff function has to satisfy certain conditions on its slope and curvature in age. However, to achieve sorting it need not be supermodular (submodular) in partners' ages, unlike in search models where the match payoff depends on the fixed type of each individual.
Keywords: C78; D83; J64; 330; Ehe; Altersgruppe; Suchtheorie; Theorie